Effects Of Oxygen Concentration On Solder Joints During Reflow Soldering - Chung, Chee Key (2003)
In this project, the effects of oxygen concentration on solder joint during reflow soldering are studied. Parameters studied include solder wetting angle, oxidation, microstructures and solder joint strength.